Peran Orang Tua dalam Mendorong Prestasi Peserta Didik di Segala Kondisi di SMPN 8 Palangka Raya - Indah Rahmawati; Misnawati Misnawati; Olga Dona Retsi; Patrisia Cuesdeyeni; Albertus Purwaka; Ita Sasmita; L. Akbar Hardin; Proyekta Oktorina; Yuliani Yuliani; Linggua Sanjaya Usop; Yuliati Eka Asi (Universitas Palangka Raya, 2025)
This research examines the role of parents in encouraging students' learning achievement at SMP Negeri 8 Palangka Raya. The purpose of this study was to determine the role of parents in encouraging student achievement in all conditions at SMP Negeri 8 Palangka Raya. The method used was descriptive method with interview techniques to two interviewee with different socio-economic backgrounds. The results showed that parents' involvement in guiding students, implementing time discipline, limiting the use of gadgets, and providing moral support and learning facilities play an important role in the success of students' academic and non-academic achievements. The challenges faced, such as time constraints and busy work schedules, both interviewee still try to support students' education through monitoring technology, open communication, and providing learning motivation. This research confirms that socio-economic status in various conditions is not the main factor that determines learner achievement, but rather the support and active involvement of parents.